A study on the factors affecting profitability of small to medium enterprises in a growing industry: the case of Novatek Animal Feeds (Private) Limited - Svova, Takudzwa (Midlands State University, 2020)
The research was aimed at studying the factors affecting profitability of small to medium enterprises. It sought to establish these factors affect profitability levels of Novatek (Pvt) Ltd as it was experiencing a decline in profitability. The research further sought to determine the ways that could be employed to improve profitability. The mixed research method , descriptive research design and a case study of Novatek Animal Feeds (Pvt) Ltd was used in the research. Interviews and questionnaires were used in the collection of data. The presentation and analysis of data was carried out in line with the research objective of the study. Pie charts , bar graphs and tables were used in the analysis and presentation of data. The major findings showed that inadequate distribution channels, increased costs, shrinking market share and increased competition result in the fall of profitability. It was recommended that Novatek should manage its cost, improve distribution channels and improve its product quality.